Case Report on Familial Maxillomandibular Synostosis- A Rare Presentation - Chaudhary, Richa; Lakhkar, Bhavana; Damke, Sachin; Lohiya, Sham (Journal of Nepal Paediatric Society, 2019)
Congenital maxillomandibular synostosis is a rare congenital deformity associated with fusion between maxilla and mandible. We report a case of a five years old child who presented with inability to open her mouth since birth. Similar history was present in the elder sister. Diagnosis of familial congenital synostosis was made and was surgically managed.